Multiple pregnancy, short cervix, part‐time worker, steroid use, low educational level and male fetus are risk factors for preterm birth in Japan: A multicenter, prospective study. Issue 1 (12th August 2013) - Shiozaki, Arihiro; Yoneda, Satoshi; Nakabayashi, Masao; Takeda, Yoshiharu; Takeda, Satoru; Sugimura, Motoi; Yoshida, Koyo; Tajima, Atsushi; Manabe, Mami; Akagi, Kozo; Nakagawa, Shoko; Tada, Katsuhiko; et al.
Abstract Aim To examine the relationship between preterm birth and socioeconomic factors, past history, cervical length, cervical interleukin‐8, bacterial vaginosis, underlying diseases, use of medication, employment status, sex of the fetus and multiple pregnancy. Methods In a multicenter, prospective, observational study, 1810 Japanese women registering their future delivery were enrolled at 8+0 to 12+6 weeks of gestation. Data on cervical length and delivery were obtained from 1365 pregnant women. Multivariate logistic regression analysis was performed. Results Short cervical length, steroid use, multiple pregnancy and male fetus were risk factors for preterm birth before 34 weeks of gestation. Multiple pregnancy, low educational level, short cervical length and part‐timer were risk factors for preterm birth before 37 weeks of gestation. Conclusion Multiple pregnancy and cervical shortening at 20–24 weeks of gestation was a stronger risk factor for preterm birth. Any pregnant woman being part‐time employee or low educational level, having a male fetus and requiring steroid treatment should be watched for the development of preterm birth.